Associations Between COVID-19 Vaccine Hesitancy and Socio-Spatial Factors in NYC Transit Workers 50 Years and Older. (January 2023) - Meltzer, Gabriella Y.; Harris, Jordan; Hefner, Michelle; Lanternier, Paula; Gershon, Robyn R.M.; Vlahov, David; Merdjanoff, Alexis A.
This analysis investigates how age, race/ethnicity, and geographic location contributed to vaccine hesitancy in a sample of 645 New York City (NYC) Transport Workers Union (TWU), Local 100 members surveyed in August 2020. Union members ages 50+ were 46% less likely to be vaccine hesitant than their younger counterparts (OR 0.64; 95% CI 0.42, 0.97). Non-Whites (OR 3.95; 95% 2.44, 6.39) and those who did not report their race (OR 3.10; 95% CI 1.87, 5.12) were significantly more likely to be vaccine hesitant than Whites. Those who were not concerned about contracting COVID-19 in the community had 1.83 greater odds (95% CI 1.12, 2.98) of being vaccine hesitant than those who were concerned. Older respondents tended to reside in Queens while vaccine hesitant and non-White respondents were clustered in Brooklyn. General trends observed in COVID-19 vaccine hesitancy persist in a population of high risk, non-healthcare essential workers.